Evaluasi Program Bantuan Operasional Sekolah Daerah Bagi Guru Tidak Tetap Di Sekolah Menengah Pertama Di Kabupaten Sekadau - Yuswa Eko Prayoga; Ida Rochmawati; Ira Patriani (LPPM STISIP IMAM BONJOL, 2026)
This study aims to evaluate the impact of the Regional School Operational Assistance Program (RSOAP) on non-permanent teachers (NPT) in junior high schools across Sekadau Rege ncy. The research explores psychological, work environment, economic, and social aspects affecting non-permanent teachers. Employing a descriptive qualitative approach, data were collected through in-depth interviews with NPTs at Public Junior High School 1 Sekadau Hilir, the school principal, an allowance officer from the Education Department, and the drafter of the Regent’s RSOAP regulation. Psychologically, many NPTs experience anxiety regarding their employment status and irregular fund disbursement, NPTs are treated equally to civil servant teachers, enjoying harmonious relationships and full participation in school activities. Economically, however, GTTs face significant challenges, including incomes below the regional minimum wage and the absence of fixed allowances, leading some to take on secondary jobs. While RSOAP is appreciated, its financial support remains insufficient to ensure economic security. Socially, recognition of professional status is viewed as secondary to financial stability, with most NPTs remaining hopeful for future civil servant status. The study concludes that while RSOAP has had a positive influence, it falls short in addressing key concerns, particularly economic hardship and employment status